HIV and AIDS - Updates on Biology, Immunology, Epidemiology and Treatment Strategies 2011
DOI: 10.5772/20751
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Testing as a Practical Tool for Rapid HIV Screening

Abstract: Saliva testing as a practical tool for rapid HIV screening. In: HIV and AIDS: updates on biology, immunology, epidemiology and treatment strategies. Intech, Rijeka, Croatia, Access from the University of Nottingham repository:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Overall, the majority of studies have demonstrated high sensitivity and specificity of oral fluid-based rapid HIV test in comparison with routinely utilized methods. [15] Clinical perspective of the article V arious studies have been conducted in the field of saliva in HIV patients, such as detection of salivary pH, buffer capacity, nitric oxide, antioxidants , and early detection of oral lesions. hence the future scope of the research is to analyze the CD4 levels in the saliva that can help in the early diagnosis of the immunodeficiency syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the majority of studies have demonstrated high sensitivity and specificity of oral fluid-based rapid HIV test in comparison with routinely utilized methods. [15] Clinical perspective of the article V arious studies have been conducted in the field of saliva in HIV patients, such as detection of salivary pH, buffer capacity, nitric oxide, antioxidants , and early detection of oral lesions. hence the future scope of the research is to analyze the CD4 levels in the saliva that can help in the early diagnosis of the immunodeficiency syndrome.…”
Section: Discussionmentioning
confidence: 99%